Proposed upgrading of Rose Suri Spa for Rose Suri Enterprise at No 18A Jalan 2/1, Taman Bernam Baru, 35900 Tanjung Malim, Perak / Amierah Kamilah Muzammil - Muzammil, Amierah Kamilah (Faculty of Architecture, Planning and Surveying, 2012)
This project is to create and provide better accommodation space for the existing spa on the first floor of corner lot and give new corporate image in order to enhance the company business and compete with other spa. The gym and aerobic class will replace by makeup service and more display products. The spa needs more privacy by installing full height partition replacing folded partition. Besides, the carpet that used as flooring has torn and worn out. A far from modern concept, muslimah concept also will be applied. The spa is concentrate on muslimah only where sometimes women ‘aurat’ is not taken seriously. Most of spa provide treatment for both men and women. Sometimes this situation brings discomfort to muslimah because they have ‘aurat’ to take care. When this concept applied, muslimah can pampered themselves without any doubt. This project aim is to create a modern design form with new corporate image that provides better design, services, and facilities for customers and staff. The objective is to create corporate identity and new concept that reflect the spa’s name and suitable as muslimah spa, so that customers can feel the relaxation in the spa. Then the spa will provide best quality of service, facilities and best management of spa to customers by creating a modern design form that provides better expression, and function for customers and staff. The space will be reorganized existing space by function and capacity of visitors at one specific time.